The business and culture of digital games gamework/gameplay - Kerr, Aphra; Sage eBooks (London : SAGE, 2006)
'Digital Games' looks at games as a new media form, the design development and marketing of games, and the use of games in public and private spaces.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Computer games -- Social aspects; Computer games -- Economic aspects; Electronic books